2017
DOI: 10.4103/ijem.ijem_418_16
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of diabetes mellitus in obese nondiabetic patients, with correlative analysis of visceral fat, fasting insulin, and insulin resistance: A 3-year follow-up study (mysore visceral adiposity in diabetes follow-up study)

Abstract: Objective:To assess the occurrence of diabetes in obese nondiabetic patients over a 3-year follow-up period with a correlative analysis of visceral fat (VF), fasting insulin levels, (FILs) and insulin resistance (IR).Material and Methods:Thirty-seven obese and nineteen nonobese nondiabetics of our previous study, Mysore Visceral Adiposity in Diabetes were followed for the next 3 years. Their blood pressure, body mass index, waist circumference (WC), fasting blood sugar (FBS), FIL, lipid profile and subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, in our study, the NC was the one that best correlated with SMM. It has recently been found that elderly people with greater NC enable the identification of overweight and obesity [ 13 , 14 ] and there is a higher risk of developing cardiovascular diseases [ 11 , 12 ]. Therefore, being more reliable than traditional risk markers, such as the BMI [ 30 ], which had a weaker correlation, and the MNA that had no correlation with the SMM equations, suggesting that anthropometric measures are more efficient for stratification of nutritional status [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study, the NC was the one that best correlated with SMM. It has recently been found that elderly people with greater NC enable the identification of overweight and obesity [ 13 , 14 ] and there is a higher risk of developing cardiovascular diseases [ 11 , 12 ]. Therefore, being more reliable than traditional risk markers, such as the BMI [ 30 ], which had a weaker correlation, and the MNA that had no correlation with the SMM equations, suggesting that anthropometric measures are more efficient for stratification of nutritional status [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the determination of the SMM may be important for the diagnosis and monitoring of pathologies related to sarcopenia and nutritional aspects [ 4 ] or for the behavior analysis of this body component in people who participate in physical exercise programs [ 10 ]. Anthropometric indicators that allow the identification of the development of heart disease [ 11 , 12 ], overweight and obesity [ 13 , 14 ] and sarcopenia [ 8 , 9 ] are used to determine the existing relationship between nontransmissible chronic diseases, obesity and muscle decrease. Therefore, considering the population aging and the increase in life expectancy for elderly people, there is a need for studies that focus on preventive measures, less expensive, to minimize body changes that occur due to inadequate aging.…”
Section: Introductionmentioning
confidence: 99%
“…It is said in a previous study that ultrasound is a reliable and easier method of measuring abdominal fat and the actual measurement of abdominal fat by ultrasound are more informative than other anthropometric measurements. [20] Our study was carried out to see whether the results in our population matches with previous studies or not.…”
Section: Discussionmentioning
confidence: 52%
“…Conflicting results have been obtained among studies attempting to address the effects of supplementation of VitD on oxidative stress. Although there have been works indicating that VitD supplementation can reduce the oxidative stress seen in cases of type 2 DM, non-alcoholic fatty liver disease, or polycystic ovarian syndrome, and even in asymptomatic individuals, there are also studies reporting that it does not affect oxidative stress [11,24,[35][36][37][38][39][40]. The effects of VitD replacement on T/DS homeostasis were not assessed in our study, but we believe that a study of the changes in T/DS homeostasis after VitD replacement would be useful in understanding relationships that may exist between VitD and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%